2021
DOI: 10.1142/s1793993321500071
|View full text |Cite
|
Sign up to set email alerts
|

Brand Love and Brand Hate: Integrating Emotions into Brand-Related Experiences and Loyalty

Abstract: Branding has always garnered substantial interest among marketers for many years. Brand love and brand hate are two aspects of branding that are drawing a great deal of attention today. Yet, there remains a gap in measuring the effect of brand love and brand hate on the relationship between brand experience and brand loyalty for the fashion apparel sector in India. Data was collected from 250 participants using both online and offline channels. Results imputed from the structural equation modeling show that br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…The findings reflect functional incongruence as a major stimulus for consumers’ negative attitudes such as dissatisfaction and brand hate ( Chon and Olsen, 1991 ; Islam et al, 2019 ). Researchers have always talked about consumers’ preferences and likely attitudes toward utilitarian aspects of products, and this study supports the notion that the functional aspects are still important for shaping consumers behaviors and emotions ( Kohli et al, 2021 ). This is even true in technological products.…”
Section: Discussionsupporting
confidence: 79%
“…The findings reflect functional incongruence as a major stimulus for consumers’ negative attitudes such as dissatisfaction and brand hate ( Chon and Olsen, 1991 ; Islam et al, 2019 ). Researchers have always talked about consumers’ preferences and likely attitudes toward utilitarian aspects of products, and this study supports the notion that the functional aspects are still important for shaping consumers behaviors and emotions ( Kohli et al, 2021 ). This is even true in technological products.…”
Section: Discussionsupporting
confidence: 79%
“…In an investigation they conducted, Bae and Kim (2023) found that brand experience affects brand love, and brand love, in turn, affects brand loyalty. They also found that brand experience affects brand loyalty, and brand love influences the relationship between brand experience and brand loyalty, which coincides with what has already been mentioned by Kohli, Khandai, Yadav, and Kataria (2021).…”
Section: Trademark Influence and Brand Experience On Consumer's Loyal...supporting
confidence: 85%
“…For their part, Kohli, Khandai, Yadav, and Kataria (2021) point out that brand love is an aspect of the brand that currently attracts much attention. However, there needs to be more in measuring the effect of brand love and brand hate on the relationship between brand experience and brand loyalty in research conducted in the fashion apparel sector in India.…”
Section: Trademark Influence and Brand Experience On Consumer's Loyal...mentioning
confidence: 99%
“…The media at large can then reach other consumers, rendering more significant these negative feelings toward the brand. Brand hate, therefore, plays a role in determining the brand's future (Kohli et al, 2021). This active negative behavior may lead to decisive action against the brand by protesting in public (Bayarassou et al, 2020).…”
Section: 4mentioning
confidence: 99%